C++ for lazy programmers : quick, easy, and fun C++ for beginners - Briggs, Will (Apress, 2019)
Learn C++ the quick, easy, and "lazy" way. This book is an introductory programming text that uses humor and fun to make you actually willing to read, and eager to do the projects, with the popular C++ language. "C++ for lazy programmers" is a genuinely fun learning experience that will show you how to create programs in the C++ language. This book helps you learn the C++ language with a unique method that goes beyond syntax and how to manuals and helps you understand how to be a productive programmer. It provides detailed help with both the Visual Studio and g++ compilers plus their debuggers, and includes the latest version of the language, C++17, too. Along the way you'll work through a number of labs: projects intended to stretch your abilities, test your new skills, and build confidence. You'll go beyond the basics of the language and learn how build a fun C++ arcade game project. After reading and using this book, you'll be ready for your first real-world C++ application or game project on your own